Developing the Halal-Tech Maturity Index for Traditional Market MSEs: A Strategy for Value-Digital Integration - Razak, Syaparuddin; Jumriani, Jumriani; Aminullah,; Musliamin,; Syamsuriadi,; Ardi, Muhammad (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2025)
This study develops the Halal-Tech Maturity Index (HTMI), a novel composite instrument that integrates halal awareness and digital readiness within traditional market-based micro and small enterprises (MSEs)—an area underexplored in current halal economy literature. The research aims to evaluate the level of halal-digital integration among MSEs, identify performance gaps, and propose a quantifiable model to guide strategic interventions in halal-based economic development. Using a mixed-methods approach, data were collected from 20 traditional markets in South Sulawesi, Indonesia through structured observation and interviews. Seven key dimensions were assessed using a 0–4 scale to construct both weighted and unweighted HTMI scores. The findings reveal a low to moderate HTMI score (1.90–1.93), indicating fragmented halal practices and limited digital adoption. However, strong interest in capacity building suggests the potential for significant improvement. Simulated interventions showed a 36.7% index increase post-training and certification support. HTMI functions not only as a diagnostic tool but also as a strategic framework for policy design, KPI monitoring, and targeted investment in halal-digital ecosystems. It bridges Islamic ethical imperatives with contemporary digital transformation agendas.